TREATMENT OF CLASS II SUBDIVISION WITH SEVERE CROWDING AND UNILATERAL SCISSOR BITE IN ADOLESCENT - Muhammad Khizfi Nurfiqoh; Dewi Sri Kartika; Avi Laviana; Ida Ayu Evangelina; Endah Mardiati (FKG ULM, 2025)
Background: Class II subdivision malocclusions in skeletal class I, characterized with a class II relation on the left side and class I on the right side along with retroclined central incisors; Case: This case presenting a 13 years-old female patient class II subdivision in skeletal class I, with severe anterior and posterior crowding, anterior crossbite, right posterior scissor bite, upper midline shift to the right, SNA 80o, dental arch asymmetry, SNB 77o, Wit’s appraisal 3 mm. Managing case: MBT.022 fixed appliances was used for this treatment, include extraction, alignment, levelling, protracting buccal segment. Resulting clockwise mandibular movement, anterior and posterior crowding, anterior crossbite, scissors bite was corrected, upper midline co-incide with lower midline, class I canine and molar, good interdigitation, and improved smile aesthetic. Treatment was completed in 31 months. Hawley retainer was use as a retention; Conclusion: This case report highlights a satisfying result of orthodontic treatment in Class II subdivision with extraction and protracting the posterior teeth and the importance of identifying the etiology in arch asymmetry cases. Keywords: class II subdivision, dental asymmetry, severe crowding